Analysis of Magneto-Poroelastic Wave Propagation Under Combined Static and Initial Stress (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the two-dimensional vibrational response of a poroelastic medium subjected to both an initial static stress state and an external magnetic field. The theoretical formulation is based on Biot’s theory of poroelasticity and incorporates electromagnetic effects through Maxwell’s equations, enabling a fully coupled description of solid deformation, pore-fluid pressure, and magnetoelastic interactions.The governing equations account for mechanical pre-stress, fluid solid coupling, magnetic body forces, and variations in pore pressure. From these equations, a generalized wave equation is derived, and closed-form solutions for displacement components, stress fields, and pore pressure are obtained for harmonic wave propagation. The influence of key material and field parameters, including porosity, permeability, magnetic field intensity, and initial stress, on wave number and frequency characteristics is systematically analyzed.Numerical results demonstrate that both magnetic loading and pre-stress significantly modify the effective stiffness of the medium, leading to noticeable changes in wave dispersion behavior. The outcomes of this work are relevant to applications in geomechanics, seismo-electromagnetic phenomena, and the development of magneto-sensitive porous materials.